OPTIMASI USAHATANI BERKELANJUTAN BERBASIS CROP LIVESTOCK SYSTEM DAN KETAHANAN PANGAN RUMAH TANGGA PETANI DI LAHAN PASANG SURUT KALIMANTAN BARAT - , AKHMAD MUSYAFAK,SP,MP; , Prof. Dr. Ir. Irham, MSc, ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Sustainable farming systems can be implemented through the crops livestock system (CLS). Implementation of this system will be achieved diversification of food products, farming efficiency, increase farmers' incomes, and food security. The objectives of the research were as follows: (a) to analyze the level of implementation of a sustainable agriculture in swamp area and the factors that influence it, (b) to analyze the degree of household food security in the swamp area and the factors that influence it, (c) to analyze optimization of farming in various both land typologies and overflow types respect to sustainable agriculture and food security based on crops livestock system (CLS), (d) to analyze the sensitivity of changes in input prices, output prices, food prices, and the use of resources, (e) to simulate changes in input prices, output prices, and food prices, to optimal models, (f) to simulate technology improvements and increased livestock scale to optimal models. The data required in this study is primary data and secondary data. Primary data were collected from the sample of farmers, while secondary data were collected from related institutions. The samples were selected using stratified random sampling. The data were analyzed using ordinary least squares, ordinal logit, and linear programming. The results of the research showed that (a) the level of implementation of sustainable agriculture in swamp area in West Kalimantan classified as sustainable enough. The factors that influence the level of sustainable agriculture were organic fertilizer, herbicides, household income, education, and ethnic (Javanese, Madurese). (b) Based on the indicators of food availability, food stability, food accessibility, food availability and continuity can be seen that there are 14% of households classified as food insecure, 37.35% of households classified as relatively less food, and 48.65% of households classified as food secure. The factors that influence to food security were land, seed prices, and the price of Urea. (c) Household income can be improved through optimization of farming. (d) The increase in input prices, output prices, and food prices were up to 30% in Kubu Raya Regency does not change the optimal solution, while the declines of output price more than 20% will change the optimal solution and household income into deficit. (g) The increase in input prices, output prices, and food prices were up to 30% in Pontianak Regency does not change the optimal solution, the declines of output price more than 10% will change the optimal solution and household income into deficit. (h) The use of recommendation technology and increased livestock scales up to 2 tail/household will achieve a state of sustainable agriculture and household food security.